Il caso Forlenza: oreficeria in bilico tra sonde spaziali, committenze vaticane e design del gioiello contemporaneo - Anastasia Segneri (Papireto)
This article aims to reconstruct, in the form of an interview, the history of the Forlenza company, a jewelry studio active in Rome since the 1960s, engaged in unexpected collaborations that go beyond the typical industry commissions. In 2005, the company expanded beyond its traditional production activities by closely collaborating with the Rome School of Aerospace Engineering, and in 2016, with the prestigious Vatican Medagliere. I have had the pleasure of getting to know Gianfranco Forlenza, born in 1942 and the founder of Forlenza Jewelry, located at 79 Via Tagliamento, in his studio-laboratory. During our conversations, which took place from November 2021 to May 2022, he recounts his long and illustrious career filled with public recognition, displaying an impressive memory for dates and figures. Today, the family tradition is carried on by Gianfranco’s two sons, Michele and Alessandro, who bring new energy to Forlenza’s production with a contemporary twist. While maintaining the distinctly artisanal character, they highlight in their jewelry the synthesis of historical craftsmanship and modern design. The company, over time, has become a well-known Roman entity recognized for its goldsmithing expertise and has been chosen for two significant commissions. In 2005, upon the request of the Rome School of Aerospace Engineering, engaged in the UniSat program focused on the design and launch of microsatellites, Forlenza produced six golden spheres for the UNISAT-4 triple spacecraft. In 2016, the Vatican Medagliere entrusted Forlenza with the restoration of 64 settings from the collection of 595 works created by the famous Italian engraver Luigi Pichler between 1819 and 1820. Originally, Emperor Francis I of Austria had commissioned the pieces to be presented as a gift to Pope Pius VII. In these restorations, and truly in all of family’s work, we see how the knowledge of traditional goldsmithing techniques and craftsmanship can effectively bridge the gap between seemingly distant worlds, enabling Forlenza to tackle unimaginable challenges.